THE IMPACT OF COMMUNAL AND THRIFT SOCIETIES ON RURAL DEVELOPMENT: A STUDY OF BIAKWAN COMMUNITY, BOKI LOCAL GOVERNMENT AREA OF CROSS RIVER STATE, NIGERIA - Ojua, Takim Asu; Audu, Demsy Terwase; Plang, Janet Punyit; Anzaku, Edward D.I. (European Scientific Journal, ESJ, 2013)
The study examines the role of communal contribution and thrift societies in the transformation of rural communities with reference to Biakwan community in Boki Local Government Area of Cross River State Nigeria. The study adopted the social survey method. Simple random sampling was use in selecting the 251 respondents that participated in the study. Key Informant Interview (KII) was also held with women, men and youth leaders within the community. The chi-square goodness-of-fit test was used to test the hypothesis at 0.05 level of confidence. Findings showed a significant relationship between participation in communal contribution and rural transformation. The recognition of already executed programmes and projects by government and subsequent encouragement of community members to continue with such transformative drive is recommended.